Mathematical Modelling As A Tool To Understand Everyday Situations (2022)
This research reports the effects derived from the application of mathematical modelling in classroom work within the development of mathematics classes, which allowed the resignification of the concept of linear function, making use of various semiotic registers of representation applied to a wide range of everyday situations. The fieldwork was based on the application of a didactic sequence to two groups of ninth grade students from a public educational institution located in the capital city of northeastern Colombia. The students were expected to build a mathematical model that would fit the data provided framed in the situations in context in order to contribute to the re-signification of mathematical knowledge. The results show that the practice of modelling favours the motivation of students in relation to mathematical knowledge, giving it meaning and significance when confronted with real situations.